Increase of operational properties of tools and machine parts nitriding the powder mixture - Kostyk, V. O.; Kostyk, K. O.; Kovalov, V. D.; Turmanidze, R.; Dašić, P. (My University, 2019)
The effect of diffusion layers and alloying elements on surface hardness, microcoarseness, and wear resistance of hardened tool steels in a nitrogen-containing medium is Studied. The experiments showed that nitriding in the powder mixture strengthens the surface layers in 2–3.5 times without reducing the volume strength of the material in question, which contributes to the preservation of high structural strength of tools and machine parts. It was found that nitriding in the dispersed powder mixture provides increased wear resistance of 1.3–2.5 times of steel, which can significantly improve the reliability and durability of products. Mathematical models of wear resistance of the investigated steels after the proposed hardening technology of nitriding are obtained.
Keywords: nitriding; powder mixture; operational properties; machine parts; diffusion layers